ANALYZING THE PLATFORM ECONOMY – FEUDALISM, MEDIEVALISM AND COLONIALISM AS USEFUL FRAMEWORKS - Jensen, Jakob Linaa; Brevini, Benedetta; Madianou, Mirca; Couldry, Nick; Mejias, Ulises (AoIR Selected Papers of Internet Research, 2021)
The platform economy challenges existing economic systems, social interactions and participation as well as the very foundation of democracy. As data is replacing labor as the central economic good, economy, society, class structures and democracy might change fundamentally. Or we might experience old wine on new bottles. Karl Marx famously said that history tends to repeat itself, first as comedy, later as tragedy. In this panel we ask, whether history is repeating itself? The panel’s speakers employ different historical perspectives but focus mainly in two periods: medieval times and the age of colonialism. Both periods were characterized by a strong correlation between a certain economic system and the exercise of political power. Structured inequalities in systems of labor, trade and distribution of wealth had significant consequences for the distribution and (re)production of political power. Medieval and colonial societies were each based on logics of exploitation and dominance, ideologically legitimized by references to first God, later the nation, what Marx would have referred to as the superstructures of economic logics. In this systems, individual agency and possibilities were limited compared to today. In medieval society it was hard to change the estate in which you were born, in colonial times it was hard to change your role in the international system. And the fixed structures were basically grounded in economic logics.